2023
DOI: 10.1021/acs.jafc.2c07680
|View full text |Cite
|
Sign up to set email alerts
|

Anthranilic Diamides Containing Monofluoroalkene Amide Linkers as Potential Insect RyR Activators: Design, Synthesis, Bio-evaluation, and Computational Study

Abstract: In order to develop anthranilic diamides with novel chemotypes, a series of anthranilic diamides with acrylamide linkers were designed and synthesized. The results of preliminary bioassays indicated that compounds with a monofluoroalkene amide linker (Z-isomer) exhibited good larvicidal activity against lepidopteran pests. The LC50 values of compound A23 against Mythimna separata and Plutella xylostella were 1.44 and 3.48 mg·L–1, respectively, while those of chlorantraniliprole were 0.08 and 0.06 mg·L–1, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 48 publications
(74 reference statements)
2
19
0
Order By: Relevance
“…Details of calcium imaging-based studies were described in our reported literature. 29 The neurons used were isolated from M. separata obtained from shallot fields in Tianjin, China. The calcium imaging protocol experiment was referenced from Takahashi's method 40 with improvements.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of calcium imaging-based studies were described in our reported literature. 29 The neurons used were isolated from M. separata obtained from shallot fields in Tianjin, China. The calcium imaging protocol experiment was referenced from Takahashi's method 40 with improvements.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These experiments were performed on M. separata neurons. Details of calcium imaging-based studies were described in our reported literature . The neurons used were isolated from M. separata obtained from shallot fields in Tianjin, China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21−23 In the structural modification of CHL (Figure 3A), several literatures mentioned that the N-containing heterocycles were used as bioisosteric substitution of the aliphatic amide moiety (part a), retaining its excellent insecticidal activities against lepidopteran pests such as Mythimna separata (M. separata) and Plutella xylostella (P. xylostella). 12,24−27 In the previous work of our group, 28,29 various diamide derivatives with excellent insecticidal activity have been obtained through innovative modifications of CHL. However, the exploration of Ncontaining heterocycles was not involved.…”
Section: ■ Introductionmentioning
confidence: 99%